Effect of Pre-Treatments and Clarificants on Sugarcane Juice Characteristics - Prasad, K.; Nath, N. (Asian Journal of Chemistry, 2010)
Enzymatic browning, sedimentation and loss of its typical flavour are the major problems encountered during storage and thermal processing of sugarcane juice. Top 5 cm of sugarcane was found to give juice of very dark colour. Therefore, it was removed before juice extraction. Topped sugarcanes were peeled to obtain juice of lower objective colour value (82.79–111.62) than juice of unpeeled samples (89.78–150.54). Natural pH of sugarcane juice was 5.6. During preparation of sugarcane juice based beverage, sugarcane juice is required to be made acidic. Acidification of sugarcane juice from the peeled samples to pH below 5 reduced colour but it was found to increase turbidity. Therefore, sugarcane juice was clarified using deaola, okra, semal and lime. Use of deola extract gave maximum clarifying effect; it reduced colour from its initial value of 98.87 to 18.49 and turbidity from 4.985 to 0.259.